2020
DOI: 10.1007/s10661-020-08293-3
|View full text |Cite
|
Sign up to set email alerts
|

Soils in lakes: the impact of inundation and storage on surface water quality

Abstract: The large-scale storage and inundation of contaminated soils and sediments in deep waterlogged former sand pits or in lakes have become a fairly common practice in recent years. Decreasing water depth potentially promotes aquatic biodiversity, but it also poses a risk to water quality as was shown in a previous study on the impact on groundwater. To provide in the urgent need for practical and robust risk indicators for the storage of terrestrial soils in surface waters, the redistribution of metals and nutrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Phosphorus in soil is dispersed among numerous geochemical phases, including soil solution and exchangeable phase, OM phase, Ca-bound phase, and Fe and Al-bound phases. The degree of P association with distinct geochemical forms greatly depends on soil physico-chemical characteristics owing to soil type, climate, and management approaches [7]. Under certain situations, these P fractions can be altered due to their different mobility, bioavailability, and chemical behaviors in soil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorus in soil is dispersed among numerous geochemical phases, including soil solution and exchangeable phase, OM phase, Ca-bound phase, and Fe and Al-bound phases. The degree of P association with distinct geochemical forms greatly depends on soil physico-chemical characteristics owing to soil type, climate, and management approaches [7]. Under certain situations, these P fractions can be altered due to their different mobility, bioavailability, and chemical behaviors in soil.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that both inorganic P and Po concentrations reduced significantly. However, much remains unknown about cropping, along with how land management techniques affect P loss and how soil aggregates sustain and cycle P pools, particularly Po [7,11]. Only few studies have examined its effects on P forms.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, turbidity information has been collected primarily through field measurement and experimental analysis [20], [21]. However, using traditional methods to estimate turbidity requires a great deal of materials, time, and human resources; and it is difficult to obtain spatiotemporal patterns [18].…”
Section: Introductionmentioning
confidence: 99%